The Use of Virtual Reality in Overcoming the State of Anxiety - V.G. Anikina; P.A. Pobokin; J.Y. Ivchenkova (Экспериментальная психология, 2021)
Modern research in the field of virtualistics concerns the problem of studying the impact of virtual reality on the state of a person’s personality. This perspective of research concerns the issue of corrective and therapeutic use of the potential of virtual reality in solving problems of practical psychology. The experimental study presented in the work is devoted to the study of the influence of virtual reality on the state of anxiety in senior schoolchildren (senior adolescence and early adolescence). In the framework of the diagnostic stage (before and after the experimental exposure), the following were used: Phillips’ School Anxiety Test and Color Sociometry. At the experimental — formative stage — schoolchildren who were diagnosed with high (17.5%) and increased levels of anxiety (30.1%) were included in a virtual reality program to overcome nytophobia. The results of the study confirmed the hypothesis of a decrease in the indicators of the state of anxiety in the study participants; the changes on the scale “General anxiety” of changes in the high level of anxiety φ* = 3.3 (p≤ 0.001) were significant. Micro-changes in color attribution values occurred for all color groups, but significant changes in preferences for self-attribution of crimson color φ* = 2.84 (p ≤ 0.05), and brown color also gave significant results φ* = 3.6 ** ( p ≤ 0.001), which may indirectly confirm changes in the state of anxiety in older students.